Peningkatan Keterampilan Sepak Sila dalam Permainan Sepak Takraw Dengan Metode Tag Games pada Mahasiswa Pendidikan Jasmani Kesehatan Rekreasi Universitas Tadulako - Didik Purwanto; Ahmad Atiq; Putra Sastaman; Muhammad Faddlika Hans Fitrianri; Akbar Nurjayadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to determine Silat's skills in the game of sepak takraw among Tadulako University Recreational Health Physical Education students. The method in this study uses a descriptive quantitative form of sports class action research. The population used in this study was 35 students. The sample used was all students using the total sampling technique. Based on the results of student research in cycle I, totaling 35 participants, there were 25 students with a total percentage of 71% and ten students who still needed to complete with a percentage of 29%. Then proceed to cycle II with 35 students obtaining 100% completeness results. In conclusion, there is an increase in the creativity of precepts in the game of takraw with the tag games method for Tadulako University Recreational Health Physical Education students.. Keywords: Skills, Sepak Takraw, Tag Games